Rural Electrification and Domestic Violence in Sub Saharan Africa - Maximiliane Sievert (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Electrification is frequently said to foster women's development and contribute to a modernization of gender roles. Using Demographic and Health Survey data from rural areas in 22 Sub-Saharan countries collected between 1999 and 2014, this paper examines the role of electricity access in reducing Intimate Partner Violence (IPV). Women in households with electricity report significantly lower acceptance of IPV. This relationship is largely driven by endogeneity, though, and applying matching and region panel approaches cast doubts on the causality of electricity for changes in attitudes towards IPV. The paper also illustrates how inference for a large number of countries is hampered by a lack of local context and observable variation, i.e. the trade-off between internal and external validity in empirical research.
Keywords: J12; J16; O13; O18; 330; rural electrification; domestic violence; intimate partner violence; region fixed effects; propensity score matching